Differential expression of microRNAs in drought-stressed sorghum roots - Hlakotsa, Ntumeleng Malefa Mamokoakoa Selinah (University of the Free State, 2024)
Sorghum (𝘚𝘰𝘳𝘨𝘩𝘶𝘮 𝘣𝘪𝘤𝘰𝘭𝘰𝘳) is an important source of food, fibre, and fuel. While it is a drought-tolerant crop, its yield is still affected by drought stress, threatening food security. Therefore, there is a need to study the drought responses of plants to develop more drought-resilient crops. This study aimed to identify drought-responsive microRNAs in sorghum roots to understand the gene regulatory processes in drought stressed sorghum. ICSB 338 (drought-susceptible) and SA 1441 (drought-tolerant) sorghum seeds were germinated and grown for three weeks with adequate watering. Subsequently, the plants were divided into two groups: A drought-stressed group, where water was withheld for 15 and 28 days to induce mild and moderate drought stress, respectively, and a control group that continued to receive adequate watering. The results showed a significant decrease in pot weight, soil moisture content, and stomatal conductance for both sorghum varieties under drought stress conditions. The leaf relative water content of ICSB 338, significantly declined following the 15 and 28 days of drought stress treatment compared to the controls. The physiological responses of the two sorghum varieties differed, with ICSB 338 being more affected by drought stress than the SA 1441. The molecular responses of sorghum to drought stress were investigated using small RNA sequencing performed on the watered controls and drought-stressed root samples of both varieties. The MGI DNBSEQ-G400 sequencing technology was used to identify the differentially expressed microRNAs. A total of 81 and 83 constitutively expressed miRNAs were identified in the watered control samples of ICSB 338 and SA 1441, respectively. Among these constitutively expressed miRNAs, 73 were common in both sorghum varieties, while eight and 10 miRNAs were unique to ICSB 338 and SA 1441, respectively. The analysis also revealed that four of the constitutively expressed microRNAs were differentially expressed between ICSB 338 and SA 1441 plants (p ≤ 0.05). The target genes of the constitutively expressed sorghum root microRNAs were predicted using the psRNATarget database, which also revealed that most of the miRNA inhibited their target genes through messenger RNA cleavage. Gene Ontology analysis of the target genes revealed that the constitutively expressed microRNAs regulate a wide range of genes with diverse cellular locations, molecular functions and biological processes in sorghum roots. Drought-responsive microRNAs (p ≤ 0.05) were identified using the CLC Genomics Workbench software (Qiagen) by comparing the watered controls and drought-stressed miRNAs using the Differential Expression for RNA-seq tool. Out of the 111 identified miRNAs in both varieties, only four and nine miRNAs were differentially expressed in ICSB 338 and SA 1441, respectively. miRNAs sbi-miR6233-3p and sbi-miR821a were up-regulated, while sbi-miR5566 and sbi-miR6224a-5p were down-regulated in ICSB 338 sorghum roots. Bioinformatics analyses predicted a 𝘗𝘶𝘵𝘢𝘵𝘪𝘷𝘦 𝘤𝘭𝘢𝘵𝘩𝘳𝘪𝘯 𝘢𝘴𝘴𝘦𝘮𝘣𝘭𝘺 𝘱𝘳𝘰𝘵𝘦𝘪𝘯 𝘈𝘵5𝘨57200 gene as a potential target for sbi-miR6233-3p, while sbi-miR821a targeted an unknown gene. The targets for sbi-miR5566 and sbi-miR6224a-5p were an 𝘜𝘯𝘤𝘩𝘢𝘳𝘢𝘤𝘵𝘦𝘳𝘪𝘻𝘦𝘥 𝘓𝘖𝘊8057912 and 𝘜𝘯𝘤𝘩𝘢𝘳𝘢𝘤𝘵𝘦𝘳𝘪𝘻𝘦𝘥 𝘓𝘖𝘊8055016, respectively. For SA 1441, two microRNAs (sbi-miR5564c-5p and sbi-miR6232b-3p) were up-regulated while seven (sbi-miR168, sbi-miR2118-5p, sbi-miR395a, sbi-miR5387b, sbi-miR5568c-3p, sbi-miR6229-5p, sbi-miR6235-5p) were down-regulated. The descriptions of the predicted target genes of SA 1441 included 𝘕𝘈𝘊 𝘥𝘰𝘮𝘢𝘪𝘯-𝘤𝘰𝘯𝘵𝘢𝘪𝘯𝘪𝘯𝘨 𝘱𝘳𝘰𝘵𝘦𝘪𝘯 83, 𝘓𝘰𝘸 𝘢𝘧𝘧𝘪𝘯𝘪𝘵𝘺 𝘴𝘶𝘭𝘧𝘢𝘵𝘦 𝘵𝘳𝘢𝘯𝘴𝘱𝘰𝘳𝘵𝘦𝘳 3, 𝘓𝘦𝘢𝘧 𝘳𝘶𝘴𝘵 10 𝘥𝘪𝘴𝘦𝘢𝘴𝘦 𝘳𝘦𝘴𝘪𝘴𝘵𝘢𝘯𝘤𝘦 𝘭𝘰𝘤𝘶𝘴 𝘳𝘦𝘤𝘦𝘱𝘵𝘰𝘳 𝘭𝘪𝘬𝘦 𝘱𝘳𝘰𝘵𝘦𝘪𝘯 𝘬𝘪𝘯𝘢𝘴𝘦 𝘭𝘪𝘬𝘦 2.1, 𝘊𝘦𝘭𝘭 𝘥𝘪𝘷𝘪𝘴𝘪𝘰𝘯 𝘤𝘺𝘤𝘭𝘦 𝘱𝘳𝘰𝘵𝘦𝘪𝘯 123 𝘩𝘰𝘮𝘰𝘭𝘰𝘨, and 𝘐𝘯𝘥𝘰𝘭𝘦-3-𝘢𝘤𝘦𝘵𝘢𝘭𝘥𝘦𝘩𝘺𝘥𝘦 𝘰𝘹𝘪𝘥𝘢𝘴𝘦. Overall, the findings of the current study contribute to our knowledge of the mechanisms sorghum uses to cope with drought stress.
Dissertation (M.Sc.(Plant Sciences))--University of the Free State, 2024
Keywords: Sorghum; Drought stress; Transcriptomics; Small RNAs; MicroRNAs; Constitutive expression; Differential expression; MGI DNBSEQ-G400 sequencing technology; miRNA target genes